DISAIN PENANGKARAN RUSA TIMOR (Cervus timorensis de Blainville) BERDASARKAN SISTEM DEER FARMING DI KAMPUS IPB DARMAGA BOGOR (Design of timor deer (Cervus timorensis de Blainville) captive breeding based on farming deer system at IPB Campus, Darmaga Bogor) - . Sumanto; Burhanuddin Masyud; AM Thohari (Department of Forest Resources Conservation and Ecotourism - IPB University, 2007)
The study was carried out to design of timor deer captive breeding based on deer farming system. The study was done to determine the feasibility of the area, optimum site allocation, and financial feasibility. According to analysis of biological component (i.e vegetation, food, predators, shelter, carrying capacity) and abiological components (i.e. topography, water, temperature and kelembaban) showed that the area were feasible to develop for timor deer captive breeding based on deer farming system. Based on management necessary, the area was divided become two zones i.e headquarter zone and captive breeding zone. Captive breeding zone were divided become 3 categories of paddocks i.e: (1) female paddock (about 1,50 ha or 35,29 % of the area, for carrying capacity about 250 female - 60 m2/head); (2) male paddock (0,35 ha or 8,24 % of the area, for carrying capacity about 341 male and 22 m2/head), and (3) offspring/rearing paddock (0,25 ha) for 1-2 year old of deer for carrying capacity about 84 deers (30 m2/head). Financial analysis showed that timor deer captive breeding was feasible to development based on farming system on maximum interest rate 18%, BCR 1,14 and IRR on 22.7 %. The bisnis of deer captive breeding was not feasible if interest rate were increase up 22.7 %.Keywords: Cervus timorensis, captive design, deer farming system, site plan, financial analysis